Garbage Monitoring Application Based On Mobile With Prototyping Method - Rio Jumardi (Journal of Telematics and Informatics, 2018)
At present, the application of information technology has developed rapidly not only in information technology based on websites and desktops but also on cellular based. Cellular phones today are no longer a luxury item. The use of cellphones has become increasingly widespread among the public. Communities as mobile phone users can use their cellular phones for various needs including being able to complain against the government. Garbage is one of the social problems faced by society. Garbage can have a bad impact on health if it is not addressed. If the garbage is disposed of carelessly it will cause various health problems in the community. Thus, more effective ways are needed to improve communication between the community and the government related to waste reports. The mobile-based garbage monitoring application is expected to be able to facilitate the public in reporting complaints and reports on social issues in this case the waste they encounter around their environment to the city government is faster, easier and resolved.